THE CHARACTERISTICS OF SCAFFOLD DESIGN FOR BONE REGENERATION : A LITERATURE REVIEW - Erlina Sih Mahanani (ODONTO : Dental Journal, 2022)
Background: Scaffold for bone regeneration is called bone graft as well, requires the proper design in order to produce new bone formation. Characteristic requirements are needed. Method: The aimed of this review to discuse the characteristics of scaffold that be needed for bone regeneration. Result: The strength of the scaffold's mechanical structure and degradation profile are adjusted to the time that take for cells to differentiate into bone cells. The swelling ability, porosity size, and interconnected porosity determine the success of incorporation of signal molecules which loaded into the scaffold. The proper selection of molecule signal is needed for stimulating cells to differentiate to be bone cells. The porosity size is adjusted to cell size, because scaffold as a micro enviroment for cells to live, grow and form a new bone. The basic ingredients of scaffold should qualify the biocompatibility standards to be accepted by the body. Scaffold is a micro enviroment for cells to produce bone matrix, and should be degraded properly after the new bone formation is formed. Conclusion: Therefore the right characteristics should be fulfilled in the design of scaffold for bone regeneration.